Phylo and Open-Phylo: A Human-Computing Platform for Comparative Genomics - Waldispuhl, Jerome; Blanchette, Mathieu (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Comparative genomics is a field of research that aims to provide us accurate mappings between the genetic material of multiple species. These techniques are useful for biomedical research and evolutionary studies. We present Phylo and Open-Phylo, an open citizen science platform and human computing-game for comparative genomic studies that reached more than 300,000 users.